Plasma microRNA-19a as a potential biomarker for esophageal squamous cell carcinoma diagnosis and prognosis. (May 2017) - Bai, Yongying; Lin, Huayue; Fang, Zanxi; Luo, Qing; Fang, Yizhen; Su, Yuanhui; Hu, Qing; Duan, Hongbing; Chen, Falin; Zhang, Zhong-Ying
Aim: To investigate whether plasma miR-19a can serve as a biomarker for esophageal squamous cell carcinoma (ESCC) diagnosis and prognosis.Materials & methods: Plasma samples from 89 ESCC, 45 benign lesion patients and 80 healthy controls were subjected to RT-qPCR analyses for miR-19a . In addition, plasma samples from 30 patients were collected before and after surgery for the same analyses.Results: Plasma miR-19a was significantly increased in ESCC patients compared with healthy controls. The sensitivity of miR-19a for early stages of ESCC was 68.09%. Combination of miR-19a and cytokeratin 19 fragment 21–1 (Cyfra21-1) further improved the sensitivity to 78.70%. Moreover, plasma miR-19a level was decreased in patients after surgery.Conclusion: Plasma miR-19a may serve as a potential biomarker that complements Cyfra21-1 in detecting early stages of ESCC.